Carcass characteristics and meat quality of swamp buffaloes (bubalus bubalis) fattened at different feeding intensities - C. Lambertz (2018)
Twenty-four male 1-year old swamp buffaloes (Bubalus bubalis) were randomly allocated to 4 groups. One group grazed on guinea grass (GG) and another on guinea grass and the legume Stylosanthes guianensis (GL). The other two groups were kept in pens and fed freshly cut guinea grass and concentrate at an amount of 1.5% (GC1.5) and 2.0% (GC2.0) of body weight, respectively. The effect of the different feeding intensities on carcass characteristics and meat quality were assessed. The mean body weight at slaughter was 398 (±16) kg. Average daily gain was higher in concentrate-supplemented groups (570 and 540 g/d in GC1.5 and GC2.0, respectively) when compared to GG (316 g/d) and GL (354 g/d) (p<0.01). Likewise, the warm carcass weight was higher in GC1.5 and GC2.0 compared to GG and GL. Dressing percentage was 48.1% and 49.5% in GC1.5 and GC2.0 in comparison to 42.9% and 44.8% observed in GG and GL, respectively. Meat of Longissimus throracis from GC1.5 and GC2.0 was redder in color (p<0.01), while water holding capacity (drip and thawing loss) was improved in pasture-fed groups (p<0.05). Protein and fat content of Longissimus thoracis was higher in animals supplemented with concentrate (p<0.01), as was cholesterol content (p<0.05), whereas PUFA:SFA ratio was higher and n-6/n-3 ratio lower (p<0.01) in pasture-fed buffaloes. Results of the present study showed that the supplementation of pasture with concentrate enhances the growth and carcass characteristics of swamp buffaloes expressed in superior dressing percentage, better muscling, and redder meat with a higher content of protein and fat, whereas animals grazing only on pasture had a more favorable fatty acid profile and water holding capacity. In conclusion, the supplementation of concentrate at a rate of about 1.5% of body weight is recommended to improve the performance and carcass quality of buffaloes. © 2014 by Asian-Australasian Journal of Animal Sciences.